2004
DOI: 10.1021/jf048434r
|View full text |Cite
|
Sign up to set email alerts
|

Differential Exudation of Two BenzoxazinoidsOne of the Determining Factors for Seedling Allelopathy of Triticeae Species

Abstract: Benzoxazinoids (Bx) are natural phytotoxins that function as chemical defense compounds in several species. The release of Bx by intact plant roots associated these compounds with root allelopathy in Triticeae species; however, the significance of exudate concentrations of Bx for plant-plant interactions is still a controversial question. A biological screening of 146 cultivars of four Triticeae species (Triticum aestivum L., Triticum durum Desf., Triticum spelta L., and Secale cereale L.) demonstrated a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 55 publications
0
77
2
Order By: Relevance
“…The presence of these allelochemicals in the rhizosphere depends on factors such as species, cultivar, or plant density (Huang et al, 2003;Belz and Hurle, 2005;Macías et al, 2014). Maybe the best estimate for naturally occurring APO concentrations can be gained from studies of exudation of the APO precursor DIBOA from roots: In hydroponic cultures, DIBOA released from rye (Secale cereale) and durum (Triticum durum) roots accumulated to concentrations of 300 and 30 µM, respectively (Belz and Hurle, 2005;Macías et al, 2014). Given the equimolar conversion of DIBOA to BOA, and a conversion rate of 10:1 of BOA into APO (Gents et al, 2005;Understrup et al, 2005), this would result in APO concentrations of 30 and 3 µM, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of these allelochemicals in the rhizosphere depends on factors such as species, cultivar, or plant density (Huang et al, 2003;Belz and Hurle, 2005;Macías et al, 2014). Maybe the best estimate for naturally occurring APO concentrations can be gained from studies of exudation of the APO precursor DIBOA from roots: In hydroponic cultures, DIBOA released from rye (Secale cereale) and durum (Triticum durum) roots accumulated to concentrations of 300 and 30 µM, respectively (Belz and Hurle, 2005;Macías et al, 2014). Given the equimolar conversion of DIBOA to BOA, and a conversion rate of 10:1 of BOA into APO (Gents et al, 2005;Understrup et al, 2005), this would result in APO concentrations of 30 and 3 µM, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The conservation of the target raises the question how the donor can avoid HDAC inhibition by its own allelochemicals. APO and AMPO are the main stable intermediates that usually develop after precursor substances have been released by plant roots into the rhizosphere; thus, these compounds are not directly produced within the donor plant itself (Belz and Hurle, 2005;Macías et al, 2006Macías et al, , 2009Belz, 2007). Accordingly, neither the APO and AMPO precursors DIBOA and DIMBOA nor the BOA and MBOA intermediates had strong effects on HDAC activity (Supplemental Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transport of allelochemicals through the CMN may also protect allelochemicals from rapid degradation by moving them away from microbial "hot zones" in the rhizosphere. Others (Belz and Hurle 2005;Tharayil et al 2009Tharayil et al , 2010) have reported diurnal fluctuations in the exudation of allelochemicals, and Thayaril and Triebwasser (2010) suggest that the pulsing of allelochemical release may be important in overcoming biotic and abiotic degradation mechanisms in soil. While we have measured greater release of thiophenes over daylight hr, the magnitude of diurnal variation seems generally modest in comparison to other variation observed in this study.…”
Section: Potential Ecological Importance Of Temporal and Spatialmentioning
confidence: 99%
“…Experiments on durum wheat and rye showed that DIBOA accumulated in the leachate at concentrations of 30 mM and 300 mM, respectively. 7,8 Taking into account a 10:1 conversion rate of DIBOA to APO, 9,10 the resulting APO concentration reaches 3 mM to 30 mM. In our previous experiments we had determined the half-maximal-effect concentration (EC 50 ) of APO to be 75 mM, 2 and thus slightly above the concentrations found in the root leachates.…”
mentioning
confidence: 99%